Nestedness and species replacement along bathymetric gradients in the deep sea reflect productivity: a test with polychaete assemblages in the oligotrophic north‐west Gulf of Mexico. (8th August 2016) - Stuart, Carol T.; Brault, Solange; Rowe, Gilbert T.; Wei, Chih‐Lin; Wagstaff, Martine; McClain, Craig R.; Rex, Michael A.
Abstract: Aim: To test the hypothesis that low productivity drives the nestedness component of β‐diversity in polychaetes at the deep‐sea floor. Location: Western Gulf of Mexico. Methods: We used A. Baselga's (2010, Global Ecology and Biogeography, 19, 134–143) metrics of species replacement and nestedness to assess their overall significance with differences in depth and particulate organic carbon (POC) flux to the seafloor. We used M. A. Rodríguez‐Gironés & L. Santamaría's (2006, Journal of Biogeography, 33, 924–935) BINMATNEST to calculate the significance and direction of nestedness with depth and POC flux. Results: Nestedness was the most significant part of β‐diversity with depth and POC flux. The rank order of nestedness increased significantly with increasing depth, and decreased significantly with increasing POC flux. There was little endemism below 2000 m. Main conclusion: The polychaete fauna in the deepest western Gulf of Mexico is largely a nested subset of the shallower upper to mid‐bathyal fauna. While the causes of β‐diversity in the deep sea are undoubtedly multivariate, the relative importance of turnover and nestedness appears to be modulated by productivity in the form of POC flux to the seafloor. Under circumstances of extremely low POC flux and animal density in the deepest reaches of the Gulf, nestedness may be caused by some populations being maintained by immigration from larger populations upslope, or by biogeographic filtering for tolerance to abyssal conditions. Resources at great depths in regions of exceptionally low productivity may be too limited to permit adaptation resulting in endemism and continued downslope turnover. If productivity helps to explain the nestedness part of β‐diversity, this may lead to a more unified theory of deep‐sea biodiversity.